Tubuh Korban Belenggu Budaya Patriarkal Menyuarakan Teologi Tubuh: Hermeneutik Trauma terhadap Narasi 2 Samuel 13:1-22 - Kayaman, Margareta Florida (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
Abstract. Women and their bodies are highly vulnerable to various acts of violence, including sexual violence. Sexual violence against women's bodies often occurs in the public sphere as well as domestic or family, especially in cultures that uphold the patriarchal system. The narrative of Tamar who was raped by Amnon (2 Sam. 13) is one narrative that represents various narratives of women who are victims of sexual violence. This paper aims to examine the narrative of the body of woman who are victim of sexual violence based on the hermeneutic of trauma developed by Christopher G. Frechette and Elizabeth Boase. This study found that Amnon, Jonadab, Absalom, David, and Tamar were all victims of the patriarchal system, but Tamar as a woman who was a victim of sexual violence, still called for respect for the human body even though it had been